Daylight - Baldacci, David (New York : Grand Central Publishing, 2020)
"FBI Agent Atlee Pine's search for her sister Mercy clashes with military investigator John Puller's high-stakes case, leading them both deep into a global conspiracy -- from which neither of them will escape unscathed"--
108491
Keywords: United States. -- Federal Bureau of Investigation -- Officials and employees -- Fiction; Missing persons -- Investigation; Organized crime; Conspiracies; Twin sisters; Serial murderers; Small cities; Murder -- Investigation; Georgia; Suspense fiction; Detective and mystery fiction; Thrillers (Fiction)